Impact of internal factors on halal food business performance: The mediating effects of halal critical point - Noor Adwa, Sulaiman; Yazkhiruni, Yahya; Mohd Sabrun, Ibrahim; Zalina, Zakaria (Emerald Publishing Limited, 2025)
Purpose - This study aims to investigate the correlation between internal factors such as halal executive competencies and commitment, management commitment, training and development, technology capabilities, cooperation and coordination, customer and supplier support, and the performance of halal food businesses, focusing on financial and operational aspects. This study also examines the mediating effect of halal critical points (HCP) on internal factors and halal food business performance. Design/methodology/approach - This study analyses 156 survey responses from halal audit management stakeholders, such as halal executives, food firm management, and JAKIM auditors, using SmartPLS. Findings - According to this study, the operational and financial performance of halal food businesses is significantly improved by internal factors such as halal executive competencies and technological capabilities, rather than aspects of customer and supplier support. Additionally, the study found no evidence to suggest that HCP played a role in mediating the relationship between internal factors and halal food business performance. Originality/value: This study reveals the links between internal factors and halal food business performance, which would help organizations improve operational efficiency and financial performance via halal food management systems.